PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS MULTIPLE INTELLIGENCES PADA MATERI SISTEM GERAK KELAS XI SMA - Fernando, Bayu; Arnentis, Arnentis; NL, Mariani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: A research was conducted to develop Multiple Intelligences-based Student Worksheets (LKPD) in the material Movement System at XI grade in Senior High School in the Teacher Training and Education Faculty of the University of Riau from October to December 2017. The research refers to the R & D research approach using the model ADDIE developed by Dick and Carry. The research was carried out until the development stage. The research subjects were KD 3.5 and KD.4.5 in the material Movement System at XI grade in Senior High School developed into 4 LKPDs for 4 meetings. Data was collected using a validation sheet filled by 5 validators, limited trials aimed at 5th semester students who had studied the Movement System as many as 15 students and limited trials aimed at high school students in XI grade as many as 20 people who had studied the Movement System material. Validation results from the aspects of content feasibility, design and pedagogic showed the four LKPDs obtained the average score of the first meeting LKPD 3.48, second meeting LKPD 3.47, third meeting LKPD 3.45, and the fourth meeting LKPD 3.57 with an overall score average of 3.46 in the category very valid. While the results of trial I on students from 4 LKPD in KD 3.5 movement system material were the first meeting LKPD 3.60, second meeting LKPD 3.60, third meeting LKPD 3.61, and fourth meeting LKPD 3.64 with overall score average was 3.61 with very good category. In the second trial of 2 LKPDs were the first meeting LKPD 3.56 and the second meeting LKPD 3.59 with an average overall score of 3.58 with a very good category. Based on the results of validation, trials and data analysis that has been done, it can be concluded that Student Intelligence Worksheet (LKPD) based on Multiple Intelligences at XI grade in Senior High School in the material Movement System has been successfully developed and obtained by very good quality LKPD and has the potential to increase Multiple Intelligences in students and can be applied in classroom learning.Key Words: Development, Student Worksheet, Multiple Intelligences